Nyíregyházán végzett népzenetanárok ön-, szakma- és jövőképe - Bíró István Ferenc (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
A magyarországi népzenetanár-képzés 1991-ben indult el a nyíregyházi Bessenyei György Tanárképző Főiskolán nappali tagozaton. Egy évvel később zárt beiskolázás keretében levelező tagozaton is megszervezték a képzést, melynek nem titkolt célja a hallgatók által már korábban megszerzett tudás legitimálása volt. Kérdőíves vizsgálatunkba kizárólag a nappali tagozaton végzett egykori hallgatókat vontuk be, melynek oka, hogy a levelező tagozatra jelentkezők többségében már megvalósult karrierrel rendelkeztek, tehát a képesítést jelentő oklevél főként az addig megvalósult karrier fenntartását jelentette. Vizsgálatainkban arra kerestük a választ, hogy hogyan lehet jellemezni a szakmai önkép, a szakmakép, valamint a közösségbe való bekötődés mértékének szempontjából azokat a kollégákat, akik rövid és hosszú távon népzenetanárként képzelik el a jövőjüket. A kapott eredmények negatív képet festenek a népzeneoktatás jövőjével kapcsolatban, ugyanis a kutatásban részt vevő pedagógusok mindössze 38 százaléka gondolkozik magáról népzenetanárként ötéves távlatban.

Abstract. Folk music teacher training started in Hungary at Bessenyei György Teacher Training College for full-time students in 1991. A year later, part-time training was also organised within the framework of a closed selection process, of which the unconcealed intention was to legitimate knowledge previously acquired by the candidates. Our questionnaire survey included former full-time students only. The reason for this was that former part-time students have already established a career, thus their qualifying degrees mainly meant the legitimation of their careers that they had previously embarked upon. The main questions were related to the ways to characterise colleagues who envision themselves as teachers of folk music in the short run and in the long run from the points of view of professional self-image, of their ideas about a career and of their involvement into the professional community. The results foreshadow a negative image concerning the future of folk music teaching. Only 38% of the colleagues participating in the survey see themselves as teachers of folk music over a five-year perspective.
The self-image concerning career and future options of folk music teachers graduating in Nyíregyháza in the light of a questionnaire survey
Keywords: Nyíregyházi Egyetem; népzenetanári képzés